Implementing a competency-based acupuncture training program in Korean Medicine education - Eunbyul Cho; Yeonkyeong Nam; Jiseong Hong; Yejin Han; Jae-Hyo Kim (PLoS ONE, 2026)
Background Acupuncture has gained global recognition as complementary and integrative therapy, but standardized education and training methods have not kept pace with its increasing application. Studies on systematic and effective acupuncture training approaches remain limited. We implemented and evaluated a newly designed acupuncture training program using a rapid prototyping instructional systems design (RPISD) model. Methods An acupuncture training program was developed using the RPISD model through needs analysis, prototype design, and development, and was then implemented with undergraduate Korean Medicine students (n = 88) in 2022/2023. Program effectiveness was evaluated through a mixed-methods design incorporating pre- and post-program assessments using a satisfaction survey, the Korean self-efficacy questionnaire measuring clinical communication skills (KSE-12), students’ practical examination score, and in-depth interviews. Quantitative and qualitative findings were integrated through a convergent mixed-methods approach to provide a comprehensive evaluation of educational effectiveness and to identify areas for improvement. Results Satisfaction was high, with 97.8% of 45 respondents expressing positive reactions to the program. Thirty-five students completed the communication questionnaire, with the total KSE-12 score significantly increasing after the course ( p = 0.028). Students especially valued the hands-on practice and peer role-play, which improved their competencies in point location and clean needle technique. Interview findings also revealed areas for improvement, including allocating more time for practice and adopting a more gradual increase in learning content. Conclusion The acupuncture training program improved students’ clinical competencies including clean needle technique, point location finding, and communication skills. This systematic approach to acupuncture education offers a replicable model for integrating traditional practices with evidence-based instructional design. The findings support broader implementation in acupuncture education programs and warrant investigation of long-term skill retention and cross-cultural applicability to advance global acupuncture training standards.